The Effects of Temperature on Development, Reproduction, Population Dynamics and Protective Enzyme Activity of Neotoxoptera formosana (Hemiptera: Aphididae) - Jiawei Liu; Yutong Feng; Weixian Yi; Changying Zheng; Lijuan Sun (Insects)
Neotoxoptera formosana is an allium vegetable pest that has increasingly threatened Chinese leek production in North China in recent years. The effects of temperature on the biological characteristics and physiology of N. formosana are not well understood. In this study, life tables were constructed at 12 °C, 16 °C, 20 °C, 24 °C, and 28 °C to explore the effects of temperature on the development, reproduction, and population dynamics of N. formosana, and to determine the threshold temperature (C) and the effective cumulative temperature (K) for each developmental stage of this aphid. The protective enzyme activity of N. formosana at three representative temperatures, 12 °C, 20 °C, and 28 °C, was determined to explore the physiological response of N. formosana to temperature. The result showed that the increasing temperature speeded up the development of N. formosana, but decreased the body size, and shortened the longevity and reproduction period of adults. The temperature exceeding 20 °C inhibited its reproduction. The N. formosana population was obviously inhibited by 28 °C with all the population parameters decreasing to be the lowest, especially the fecundity, which was 16.7 times lower than that at 20 °C. The population expanded the fastest at 20 °C, followed by 24 °C, 16 °C, and 12 °C, the slowest at 28 °C, with the population size merely increasing to 2.3 times at 60 days. The K values for the first, second, third, and fourth-instar nymphs were 1.852 °C, 5.029 °C, 4.747 °C and 5.979 °C, respectively, and the C values were 47.540 days °C, 30.817 days °C, 33.481 days °C and 32.294 days °C, respectively. The C value for nymphal aphids was 4.002 °C, and the K value was 145.252 days °C. The activity of superoxide dismutase and peroxidase of N. formosana at 28 °C was higher than at 12 °C and 20 °C, and the catalase activity of N. formosana was highest at 12 °C. In conclusion, the temperature had significant effects on population parameters and the physiological metabolism of N. formosana.